Digital Identity and Moral Negotiation among Salafiyah Students in the Social Media Spaces - Damanhuri; Abdurrahman; Hasnan Bachtiar (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This research aims to analyze the digital identity of Salafiyah santri (Islamic boarding school students) amidst the pervasive use of social media such as TikTok, Instagram, and YouTube. Initially regarded as a space for entertainment and information, social media has now become an arena for self-expression and Islamic proselytization (dakwah) for some santri. However, these digital activities often come into tension with the core values of the pesantren (Islamic boarding school), particularly zuhud (asceticism or simplicity) and tawadhu' (humility), which reject excessiveness and self-promotion. This research employs a descriptive qualitative approach, utilizing Giddens' theory of reflexive identity and Goffman's dramaturgical theory to understand how santri form and negotiate their self-image in the digital realm. Preliminary findings indicate that the santri experience moral ambivalence: on one hand, they strive to spread Islamic values through digital dakwah content, yet on the other hand, they grapple with the pressure to appear popular and appealing in the eyes of the online public. The study is expected to contribute to the development of a digital ethic for santri as part of the broader transformation of pesantren culture in the digital era